Preferences of Vocational High School (SMK) Students at The Main Branches of Mathematics - Endro Tri Susdarwono (Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Jember, 2022)
This study uses a quantitative approach, hypothesis testing through chi-square distribution by applying the goodness of fit testing method. The goodness of fit test is also called the goodness of fit test. In a real sense, the goodness of fit test is a hypothesis testing by comparing the observed frequency with the expected frequency. Regarding the goodness of fit of a frequency distribution of observations, the calculation is based on the average value and the frequency of observations. Furthermore, hypothesis testing is carried out to determine whether the frequency distribution of the observed results is in accordance with the expected frequency distribution. Based on the goodness of fit testing procedure that uses the chi-square distribution, it can be concluded that there are differences in the preferences of Vocational High School (SMK) students towards the main mathematics variants. Students do not perceive that all major areas of mathematics are the same. It is possible that certain fields in the fields of mathematics contain material that students find difficult, so students prefer other fields that students tend to master or are easier.